EFFICACY OF ORNIDAZOLE GEL AS AN ADJUNCT TO SCALING AND ROOT PLANING IN CHRONIC PERIODONTITIS PATIENTS: A CLINICAL AND MICROBIOLOGICAL STUDY. - P.INDEEVAR5M.NAGASREE1, P.BINDU MADHURI2, S.V.V.S MUSALAIAH3, P.ARAVIND KUMAR4 (Journal of Biomedical and Pharmaceutical Research, 2016)
INTRODUCTION: Periodontitis is an inflammatory disease of the supporting tissues of teeth caused by specific group of microorganisms resulting in destruction of periodontal ligament, alveolar bone with pocket formation, recession or both. AIM: To evaluate the efficacy of Ornidazole gel as adjunct to scaling and root planning in chronic periodontitis patients. MATERIALS AND METHODS: A split mouth study was done in ten patients having probing pocket depths of ≥4 mm and diagnosed with chronic periodontitis with atleast two sites, each site is randomly assigned to either SRP+Ornigreat(Group A) or SRP alone(Group B). Assessment of plaque index (PI), gingival index (GI), probing pocket depth(PPD), and clinical attachment levels (CAL) was done at baseline and 3 months. Microbiologic assessment with polymerase chain reaction was done for Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola by collection of plaque samples. RESULTS: Both the groups A and B have shown statistically significant results in terms of all clinical and microbial parameters pre operatively and post operatively with more significance observed in Group A CONCLUSION: Group A which was treated with Ornidazole + SRP had shown better efficacy in terms of all clinical parameters and microbial analysis when compared to that of Group B who were treated with SRP alone. Keywords: Periodontitis, Ornidzole gel, Scaling and root planing, Microbial analysis.